Cross-Regional Educational Governance: Lessons from Higher Education Reform in Asia and Europe - Louis De Smet (PT. Islamic Research Publisher, 2024)
This study examines the dynamics of cross-regional educational governance by analyzing higher education reform in selected countries in Asia and Europe. The research aims to identify how governance models, policy frameworks, and institutional reforms shape the transformation of higher education systems across different regional contexts, and to explore the transferable lessons that can inform global higher education governance. Using a qualitative comparative research design, this study employs a systematic literature review and policy analysis of major higher education reforms implemented in both regions. Data were collected from academic publications, policy documents, and international reports published by global education organizations, and analyzed through thematic and comparative approaches to identify patterns of governance reform. The findings reveal three key patterns. First, European higher education reforms are strongly influenced by regional policy coordination and supranational frameworks that promote standardization, mobility, and quality assurance across national systems. Second, Asian higher education reforms tend to emphasize state-driven modernization, institutional autonomy within centralized policy frameworks, and strategic internationalization to enhance global competitiveness. Third, despite differences in political and institutional contexts, both regions demonstrate a growing convergence toward governance models that prioritize accountability, quality assurance mechanisms, global collaboration, and innovation-driven academic ecosystems. This study contributes to the literature on global higher education governance by providing a cross-regional comparative framework that highlights the interaction between regional policy coordination, national governance structures, and institutional reform strategies. The research also offers policy-relevant insights for emerging higher education systems seeking to balance global competitiveness with local governance realities. By synthesizing lessons from Asia and Europe, the study advances a more nuanced understanding of how multi-level governance structures influence the transformation and sustainability of higher education systems in the contemporary global knowledge economy.